Telehealth and racial disparities in colorectal cancer screening: A pilot study of how virtual clinician characteristics influence screening intentions - Eric J. Cooks; Kyle A. Duke; Jordan M. Neil; Melissa J. Vilaro; Danyell Wilson-Howard; Francois Modave; Thomas J. George; Folakemi T. Odedina; Benjamin C. Lok; Peter Carek; Eric B. Laber; Marie Davidian; et al. (Journal of Clinical and Translational Science, 2022)
Abstract